Knowledge and practices related to antimicrobial use in fighting cocks – a survey of fighting cock owners in Timor-Leste - Pereira, Abrao J.; Amaral, Frederico; Coppo, Mauricio J. C.; Bailey, Kirsten E.; Ting, Shawn; Gilkerson, James; Browning, Glenn F.; Jong, Joanita Bendita D. C.; Toribio, Jenny-Ann L. M. L. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionCock fighting is an industry with a long standing in Southeast Asia and the birds have a high value. However, there is scant published literature on antimicrobial use and knowledge about antimicrobial resistance (AMR) among fighting cock owners in Timor-Leste. This survey assessed knowledge of fighting cock owners about antimicrobials and AMR, and their use of antimicrobials in fighting cocks.MethodThis was a cross-sectional survey conducted on randomly selected owners of fighting cocks in urban areas in Timor-Leste between February and March 2023. Data collection was done using a structured questionnaire administered by face-to-face interviews.ResultsA total of 275 participants were interviewed. Knowledge about antimicrobials and AMR among fighting cock owners in Timor-Leste was poor. Owners in urban areas (aOR = 2.4, 95% CI [1.4-4.1], p-value = 0.002) and those with higher education (aOR = 2.3, 95% CI [1.3-4.2], p-value = 0.007) were more knowledgeable about antimicrobials. The majority used antimicrobials (76.2%, 205/269) in their cocks and the most common antimicrobials used were amoxicillin (77.5%, 159/205) and ampicillin (54.2%, 111/205). The most common reasons for use were for treating fight wounds (85.4%, 175/205), respiratory signs (26.3%, 54/205), and diarrhea (21.0%, 43/205).ConclusionThis study revealed widespread antimicrobial use by fighting cock owners with low awareness about AMR, which creates a high-risk environment for selection for emergence of AMR. There is a need for a comprehensive intervention that combines regulatory controls, enhanced surveillance, and a targeted campaign to mitigate public health risks in Timor-Leste.